2019
DOI: 10.3846/jeelm.2019.11561
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing and Modeling the Spatiotemporal Dynamics of Urban Expansion: A Case Study of Hangzhou City, China

Abstract: Understanding the spatiotemporal characteristics of urban expansion is increasingly important for assisting the decision making related to sustainable urban development. By integrating remote sensing (RS), spatial metrics, and the cellular automata (CA) model, this study explored the spatiotemporal dynamics of urban expansion and simulated future scenarios for Hangzhou City, China. The land cover maps (2002, 2008, and 2013) were derived from Landsat images. Moreover, the spatial metrics were applied to charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Lin and Ling (2021) found that the ULUE in the Yangtze River Delta has steadily improved, and the spatial difference has gradually expanded [13]. Zhao et al (2019) suggested that urban land use in Hangzhou shows an expanding tendency, and its spatial characteristics have become more complex [14]. Zhu et al (2019) proved the heterogeneity between cities in terms of ULUE and found that economic level and infrastructure promote efficiency improvement [15].…”
Section: Introductionmentioning
confidence: 99%
“…Lin and Ling (2021) found that the ULUE in the Yangtze River Delta has steadily improved, and the spatial difference has gradually expanded [13]. Zhao et al (2019) suggested that urban land use in Hangzhou shows an expanding tendency, and its spatial characteristics have become more complex [14]. Zhu et al (2019) proved the heterogeneity between cities in terms of ULUE and found that economic level and infrastructure promote efficiency improvement [15].…”
Section: Introductionmentioning
confidence: 99%